Mangrove rare actinobacteria: taxonomy, natural compound, and discovery of bioactivity - Azman, Adzzie-Shazleen; Othman, Iekhsan; S. Velu, Saraswati; Chan, Kok-Gan; Lee, Learn-Han (Frontiers in Microbiology, 2015)
Actinobacteria are one of the most important and efficient groups of natural metabolite producers. The genus Streptomyces have been recognized as prolific producers of useful natural compounds as they produced more than half of the naturally-occurring antibiotics isolated to-date and continue as the primary source of new bioactive compounds. Lately, Streptomyces groups isolated from different environments produced the same types of compound, possibly due to frequent genetic exchanges between species. As a result, there is a dramatic increase in demand to look for new compounds which have pharmacological properties from another group of Actinobacteria, known as rare actinobacteria; which is isolated from special environments such as mangrove. Recently, mangrove ecosystem is becoming a hot spot for studies of bioactivities and the discovery of natural products. Many novel compounds discovered from the novel rare actinobacteria have been proven as potential new drugs in medical and pharmaceutical industries such as antibiotics, antimicrobials, antibacterials, anticancer and antifungals. This review article highlights the latest studies on the discovery of natural compounds from the novel mangrove rare actinobacteria and provides insight on the impact of these findings.